1966
DOI: 10.1063/1.1726543
|View full text |Cite
|
Sign up to set email alerts
|

Negative Fragment Ions from Resonance Capture Processes

Abstract: An examination of negative fragment ions formed by resonance capture processes has been made using a mass spectrometer. It has been found in some cases that the various fragments for a particular molecule arise at the same ionizing energy, possibly by competing decomposition paths from the same state of the n;gative molecular ion. Other cases where the fragments do not arise at exactly the same energy may be explamed by close upper energy states of the negative molecular ion.. In general the observed ionizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
62
1

Year Published

1969
1969
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 30 publications
16
62
1
Order By: Relevance
“…It may be due to multiple fragmentation. Dorman [15] and Tsuda et al [21] observed CI-in the energy range between 6 and 9eV in agreement with our observation. Presumably, the resonance in the CH,CI--cross section is due to the dissociative attachment process e-+ CH,CI + CH,CI-+ H .…”
Section: Chscisupporting
confidence: 93%
“…It may be due to multiple fragmentation. Dorman [15] and Tsuda et al [21] observed CI-in the energy range between 6 and 9eV in agreement with our observation. Presumably, the resonance in the CH,CI--cross section is due to the dissociative attachment process e-+ CH,CI + CH,CI-+ H .…”
Section: Chscisupporting
confidence: 93%
“…4 occurred in the higher electron energy range. In the presence of water vapor, H-, 0-, OHwould be produced from the dissociative electron attachment to H,O (Moruzzi and Phelps, 1966;Massey, 1976;Schulz, 1960;Compton and Christophorou, 1967;Dorman, 1966). Those reactions consume electrons and decrease the collisions of electrons to sulfur compound molecules.…”
Section: Removal Mechanismmentioning
confidence: 97%
“…Measured cross sections for vibrational excitation by electron impact have shown both the π * resonance [10,11], at about 1.2 eV, and a further broad peak at 6.8 eV, assigned to one or more σ * resonances [10]. Other measurements have determined thresholds and, in some cases, relative cross sections for electronic excitation [8,10,[12][13][14][15][16], while still others have examined dissociative electron attachment [10,[17][18][19] and electron-impact ionization [20][21][22]. Burean and Swiderek [23] have studied the chemistry induced in condensed acetaldehyde by low-energy electron impact.…”
Section: Introductionmentioning
confidence: 99%